The Ability of Some Polysaccharides to Disaggregate Lysozyme Amyloid Fibrils and Renature the Protein - Olga Makshakova; Liliya Bogdanova; Dzhigangir Faizullin; Diliara Khaibrakhmanova; Sufia Ziganshina; Elena Ermakova; Yuriy Zuev; Igor Sedov (MDPI AG, 2023)
The deposition of proteins in the form of insoluble amyloid fibril aggregates is linked to a range of diseases. The supramolecular architecture of such deposits is governed by the propagation of β-strands in the direction of protofilament growth. In the present study, we analyze the structural changes of hen egg-white lysozyme fibrils upon their interactions with a range of polysaccharides, using AFM and FTIR spectroscopy. Linear anionic polysaccharides, such as κ-carrageenan and sodium alginate, are shown to be capable to disaggregate protofilaments with eventual protein renaturation. The results help to understand the mechanism of amyloid disaggregation and create a platform for both the development of new therapeutic agents for amyloidose treatment, and the design of novel functional protein-polysaccharide complex-based nanomaterials.